Measuring Score of Ethnic Tolerance Index among Peacekeepers using a MyETI System Dashboard - Wan Husin, Wan Norhasniah; Kamarudin, Nur Diyana; Hilmi, Muhammad Amjad; Zainurin, Siti Juwairiah; Jamilah, Maryam (JOIV : International Journal on Informatics Visualization, 2024)
In post-conflict nations, the state-building process might take up to ten years to provide positive outcomes. This scenario has become increasingly challenging due to the escalation of intolerance among different ethnic groups, leading to incidents of communal violence in the aftermath of the war. Therefore, it is imperative to have ethnic tolerance and cultural understanding in peacekeeping operations that occur in a more intricate setting. The presence of ethnic tolerance among peacekeepers is crucial for ensuring the efficacy of peacekeeping missions. The increase of intolerant perspectives often causes the beginning of ethnic conflicts in multi-ethnic societies. Therefore, the main objective of peacekeepers deployed in these countries is to reinstate peace and security. This study proposes employing an online analysis to assess the ethnic tolerance index among peacekeepers accurately. The suggested method entails collecting and analyzing real-time survey data via a MyETI system dashboard, which may precisely evaluate the ethnic tolerance index score among Malaysian individuals. The MyETI e-survey has 103 questionnaires organized into four main categories: ethnic cross-relationships, governance, ethnic tolerance, and religious beliefs. To achieve the study's goal, 103 Malaysian peacekeepers who have previously been deployed to different United Nations Peacekeeping Operations (UNPKO) will be requested to answer the questions using the MyETI dashboard. The results could enhance the ethical guidelines for cultural competence, prioritizing understanding ethnic tolerance in peacekeeping operations or deployments.